Extracellular Vesicles from MSC Modulate the Immune Response to Renal Allografts in a MHC Disparate Rat Model - M. Koch; A. Lemke; C. Lange (Hindawi Limited, 2015)
Application of mesenchymal stromal cells (MSC) has been proposed for solid organ transplantation based on their potent immunomodulatory effects. Since side effects from the injection of large cells cannot be excluded, the hypothesis rises that extracellular vesicles (EV) may cause immunomodulatory effects comparable to MSC without additional side effects. We used MSC-derived EV in a rat renal transplant model for acute rejection. We analysed peripheral blood leukocytes (PBL), kidney function, graft infiltrating cells, cytokines in the graft, and alloantibody development in animals without (allo) and with EV application (allo EV). There was no difference in kidney function and in the PBL subpopulation including Tregs between allo and allo EV. In the grafts T- and B-cell numbers were significantly higher and NK-cells lower in the allo EV kidneys compared to allo. TNF-α transcription was lower in allo EV grafts compared to allo; there was no difference regarding IL-10 and in the development of alloantibodies. In conclusion, the different cell infiltrates and cytokine transcription suggest distinct immunomodulatory properties of EV in allotransplantation. While the increased T- and B-cells in the allo EV grafts may represent a missing or negative effect on the adaptive immune system, EV seem to influence the innate immune system in a contrary fashion.